Hirsutism, Acne, and Hair Loss: Management of Hyperandrogenic Cutaneous Manifestations of Polycystic Ovary Syndrome - Yasa, Cenk; Dural, Özlem; Bastu, Ercan; Uğurlucan, Funda Güngör (Gynecology Obstetrics & Reproductive Medicine, 2017)
PPolycystic ovary syndrome is the most common endocrine abnormality that affects reproductive-aged women. Diagnostic criteria of polycystic ovary syndrome have been established by different societies in recent years, and hyperandrogenism remains as one of the main criteria for diagnosis. Cutaneous manifestations of hyperandrogenism include hirsutism, acne and androgenic alopecia and are commonly observed in women with polycystic ovary syndrome. The major determinants of cutaneous manifestations are increased production of androgen and increased tissue availability. Cutaneous manifestations of hyperandrogenism are cosmetic problems, which produce significant emotional distress and psychological morbidity. Treatment includes a combination of combined oral contraceptives, antiandrogens, insulin sensitizers, gonadotropin releasing hormone agonists, topical medications, and cosmetic procedures. The diagnosis, management, and treatment approaches are described in detail in this review.